In Vitro Secretion Deficits are Common Among Human Coagulation Factor XIII Subunit B Missense Mutants: Correlations with Patient Phenotypes and Molecular Models. Issue 11 (13th September 2013) - Biswas, Arijit; Thomas, Anne; Bevans, Carville G.; Ivaskevicius, Vytautas; Oldenburg, Johannes
Abstract : Pairs of coagulation factor XIII (FXIII) B subunits bound to A dimers prior to activation are thought to possess carrier/protective function. Mutations in either A or B subunits are associated with pathological patient phenotypes of mild to severe bleeding. HEK293T cell expression studies of seven recently identified FXIIIB missense variants revealed impaired in vitro secretion phenotypes. Molecular models of FXIIIB Sushi domains constructed using phylogenetically similar complement factor H Sushi domain templates suggest possible pathological mechanisms. ABSTRACT: Coagulation factor XIII (FXIII) proenzyme circulates in plasma as a heterotetramer composed of two each of A and B subunits. Upon activation, the B subunits dissociate from the A subunit dimer, which gains transglutaminase activity to cross‐link preformed fibrin clots increasing mechanical strength and resistance to degradation. The B subunits are thought to possess a carrier/protective function before FXIII activation. Mutations in either A or B subunits are associated with pathological patient phenotypes characterized by mild to severe bleeding. In vitro expression of FXIII B subunit (FXIIIB) missense variants in HEK293T cells revealed impaired secretion for all seven variants studied. To investigate the likely molecular environments of the missense residues, we created molecular models of individual FXIIIB Sushi domains using phylogenetically similar complement factor H Sushi domain structural templates. Assessment of the local molecular environments for the models suggested surface or buried positions for each mutant residue and possible pathological mechanisms. The in vitro expression system and in silico analytical methods and models we developed can be used to further investigate the molecular basis of FXIIIB mutation pathologies.